EFEKTIVITAS HUKUM PERKAWINAN DALAM MENEKAN ANGKA PERCERAIAN DI INDONESIA - Damayanti; Fitria Agustin (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the effectiveness of marriage law in reducing divorce rates in Indonesia and to identify the factors influencing its level of effectiveness. Marriage law in Indonesia is regulated under Law Number 1 of 1974 concerning Marriage, which aims to establish a happy and enduring family. However, in practice, divorce rates continue to show an increasing trend. Data from Statistics Indonesia recorded 438,168 divorce cases in 2025. This research employs a qualitative approach with a normative juridical method and a descriptive-analytical nature. The data were obtained through literature study by analyzing statutory regulations, legal theories, and relevant academic sources. The results indicate that marriage law in Indonesia has not been fully effective in reducing divorce rates. This is influenced by several factors, including the substance of the law that is not fully responsive, the role of law enforcement, low public legal awareness, limited facilities and infrastructure, as well as changes in social values and norms. Nevertheless, the law still plays an important role in regulating and providing legal protection for the parties, particularly in divorce proceedings and their legal consequences. Therefore, more comprehensive efforts are needed through regulatory improvements, enhancement of public legal awareness, and strengthening the role of social institutions to increase the effectiveness of marriage law in maintaining family integrity in Indonesia.